La crisis de más de cuarenta años: Una historia global reciente - Simonoff, Alejandro (Biblioteca de Humanidades, 2021)
The crisis of more than forty years: A recent global history: In a dialogue between History and studies in International Relations, this recent global history begins with the Cold War and the French May '68 uprisings; it continues with the 1973 oil crisis, which, although initially undervalued and disparaged as an increase in the price of oil, is addressed due to its impact on the course of the century and the political responses it generated: the rise of the New Right in the First World, the Soviet Perestroika, the Four Modernizations in China and the Iranian Revolution. Subsequently, the book covers unfinished transitions: the pretension of a unipolar world, the failed World Order and its conflicts, the 2008 crisis and the search for global governance after the crack.